PENGARUH UKURAN PERUSAHAAN, SALES GROWTH, DAN OPERATING CAPACITY TERHADAP FINANCIAL DISTRESS. - Andrew p, Enrico; Bangun, Nurainun (Jurnal Paradigma Akuntansi, 2025)
The purpose of this study is to obtain empirical evidence regarding the effect of company size, sales growth, and operating capacity on financial distress. This research uses food and beverage sector companies listed on the Indonesia Stock Exchange in 2020-2022. This research uses a purposive sampling method and there are as many as 93 company data. The data obtained was processed using the E-Views 12 program. Based on the research conducted, the results obtained were that company size has a positive and significant impact on financial distress, sales growth has a negative and significant impact on financial distress, and operating capacity has a positive and significant impact on financial distress. The implication of this research is that company size, sales growth, and operating capacity affect company management, investors, and creditors in making decisions.